Prevalence of ECG abnormalities and risk factors for QTc interval prolongation in hospitalized psychiatric patients. (December 2019) - Ansermot, Nicolas; Bochatay, Meredith; Schläpfer, Jürg; Gholam, Mehdi; Gonthier, Ariane; Conus, Philippe; Eap, Chin B
Background: Psychiatric patients are at risk of cardiovascular diseases, and many psychotropic drugs can prolong QTc interval. Requirements for electrocardiogram (ECG) monitoring have been set up in our psychiatric university hospital. The objective of this study was to determine the proportion of adult patients who had an ECG during their hospitalization, the prevalence of ECG abnormalities, the evolution of the QTc after admission, and the risk factors for QTc prolongation. Methods: Retrospective analysis of ECGs and clinical data of all patients with a complete hospitalization in 2015. Assessment of the influence of covariates on QTc using linear mixed-effects models. Results: At least one ECG ( n  = 600) was performed during 37.6% of the stays ( n  = 1198) and in 45.5% of the patients ( n  = 871). Among the patients with an ECG, 17.9% had significant ECG abnormalities, including 7.6% with a prolonged QTc. QTc measured at admission and during hospitalization did not change significantly ( n  = 46, 419.4 ± 29.7 ms, 417.2 ± 27.6 ms, p  = 0.71). In the multivariate model (292 patients, 357 ECGs), the covariates significantly associated with the QTc were gender (+15.9 ms if female, p  < 0.0001), age (+0.4 ms/year, p  = 0.0001), triglyceride levels (+5.7 ms/mmol/l, p  = 0.005), and drugs with known risk of torsades de pointes (+6.2 ms if ⩾1 drug, p  = 0.028). Conclusions: The prevalence of hospitalized psychiatric patients with an abnormal ECG indicates that ECGs should be performed systematically in this population. Prescription of psychotropic drugs should be done cautiously, particularly in patients with QTc prolongation risk factors.